Multiple Dimensions of Academic Language and Literacy Development. (13th February 2013) - Cumming, Alister
Abstract : Language, literacy, and culture intersect almost everywhere, of course. I analyze three phenomena where intersections occur between cognitive skills, personal attitudes, social practices, and macro‐societal structures in ways that are salient, puzzling, and also illuminating about the multiple dimensions of learning literacy in situations of cultural and linguistic diversity: (a) heuristic search strategies involving language switching for choices of words and phrases while composing, (b) expressions of personal identity when writing for specific discourse communities, and (c) reciprocal modeling during dynamic assessments of writing and reading. Examples are drawn from research in Toronto with multilingual students entering university programs and with "at‐risk" adolescents in a community‐based, after‐school tutoring program. The analyses set an agenda for future research and educational practices to help develop the multifaceted dimensions of developing academic literacy among culturally diverse learners.